Metabolic pathways regulated by TAp73 in response to oxidative stress - Agostini, Massimiliano (Oncotarget, 2016)
Reactive oxygen species are involved in both physiological and pathological processes including neurodegeneration and cancer. Therefore, cells have developed scavenging mechanisms to maintain redox homeostasis under control. Tumor suppressor genes play a critical role in the regulation of antioxidant genes. Here, we investigated whether the tumor suppressor gene TAp73 is involved in the regulation of metabolic adaptations triggered in response to oxidative stress. H(2)O(2) treatment resulted in numerous biochemical changes in both control and TAp73 knockout (TAp73−/−) mouse embryonic fibroblasts, however the extent of these changes was more pronounced in TAp73−/− cells when compared to control cells. In particular, loss of TAp73 led to alterations in glucose, nucleotide and amino acid metabolism. In addition, H(2)O(2) treatment resulted in increased pentose phosphate pathway (PPP) activity in null mouse embryonic fibroblasts. Overall, our results suggest that in the absence of TAp73, H(2)O(2) treatment results in an enhanced oxidative environment, and at the same time in an increased pro-anabolic phenotype. In conclusion, the metabolic profile observed reinforces the role of TAp73 as tumor suppressor and indicates that TAp73 exerts this function, at least partially, by regulation of cellular metabolism.